Need of Islamization of Education for Sustainable Development - Baqui, Md Abdullahel (IIUC Studies, 2015)
At the beginning, the paper discussed about the Position of human being in the universe according to modern science and islamic perspective. Secondly, Significance of knowledge is highlighted as the main reason behind mans highest status among the creations. Brief description is given on how knowledge came to man and what are the basic issues. Thirdly, the most notorious barrier against mans knowledge gain is identified and a short account on the mechanism of its action is given. Then came, how mans enemy starts setting its trap by distorting the Education System. How his desires are reflected in the concept curriculum teaching techniques and evaluation of almost all modern academic institutes together with its tragic impact on Development of man and society are exemplified. Critical evaluations are done on the role of traditional Islamic institutes and finally, suggestions are given on how to bring back the scenario of real development through islamization of education. IIUC Studies Vol.9 December 2012: 107-112